Analog Layout Generation for Performance and Manufacturability - Lampaert, Koen ((The Kluwer International Series in Engineering and Computer Science ; Analog Circuits and Signal Processing))
Contenido: 1) Introducción; 2) Resultados de modificación del diseño de circuitos integrados analógicos; 3) Módulo de generación; 4) Colocación; 5) Ruteo; 6) Implementación; 7) Conclusiones generales.